Merton's East-West Reflections - Carr, Anne E. (Horizons, 1994)
While the writings of Thomas Merton sustain their popularity twenty-five years after his untimely death, his later reflections on Eastern religions have led some to believe he was no longer really a Christian in his last years. This article places the question within the current discussion of Christianity and other religions and then argues for the centrality of Merton's Christianity in his appropriation of other traditions of transformation. It does this by underscoring his focus on experience rather than doctrine and suggesting the abiding Christian center of that appropriation.